Družbena želenost in težnja k soglašanju v družboslovnem raziskovanju - Uhan, Samo (Teorija in praksa, 1998)
Social survey researchers have realized for number of years that various response sets might have considerable influence on expressed opinions. Accordingly, we have to abandon the belief that the instrument is a neutral stimulus which provokes a reaction that has only to be recorded objectively. This holds all the more so when the topic is highly abstract and thus penetrates to the forefront of the respondent's psychic and symbolic structuralization. A phenomenon which is not exclusive to public opinion research is elucidated by Couch and Keniston (Kouch & Keniston 1964) in a study of 'the tendency to acquiesence'. The analysis of survey responses shows this tendency to be a personality variable, that is, a manifestation of the respondent's style and psychic structure. The authors find a high level of a priori congruity of responses irrespective of the content. On the other hand, social desirability is generaly considered to be a major source of response bias in survey research. Given the frequency with which them is mentioned as a cause, explanations of it are suprisingly rare in the literature. Generally speaking, it refers to a tendency to give favourable picture of onself (DeMaio 1985).
Keywords: javno mnenje; anketiranje; teorija; theory; družboslovno raziskovanje; metodologija; družbena želenost